PENGEMBANGAN MEDIA AUDIO VISUAL BERBANTU APLIKASI CANVA MATERI BANGUN RUANG LIMAS - Kayati, Nur; Ain, Siti Quratul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This study focuses on obtaining valid canva-based audio-visual teaching materials, so that they can be said to be suitable for use in the learning process. This type of research is research and development (Research and Development) where the design uses the ADDIE model development which has been simplified into several stages, namely analysis, design, development. The data collection instrument used is the expert validation sheet. Data collection techniques are validation sheets, observations and unstructured interviews. Qualitative descriptive analysis is the data analysis method used, and tries to characterize the validity findings provided by the validator. The results of the data analysis obtained validity in the aspects of material, language, and design. The characteristics of the validator results are respectively 83.63%, 86.25%, 88% with the category